Comparison Between K3EDTA and Lithium Heparin as Anticoagulant to Isolate Bovine Granulocytes From Blood - Baien, Shima Hassan; Langer, Melissa Natalie; Heppelmann, Maike; von Köckritz-Blickwede, Maren; de Buhr, Nicole (Frontiers in Immunology, 2018)
Granulocytes play a key role in the defense against invading pathogens. To study granulocyte functions, the isolation of a pure and active cell population from fresh blood is required. Anticoagulants and red blood cells (RBCs) lysis used in the isolation procedure may influence cell harvest, cell marker expression and pre-activation of cells. In this study, the influence of the anticoagulants K3EDTA or lithium heparin and the effect of different RBCs lysis methods on bovine granulocyte population from fresh blood of healthy cows after density gradient centrifugation were investigated. Venous blood from healthy cows was collected in K3EDTA and lithium heparin tubes. Density gradient centrifugation to separate granulocytes from other cells was conducted using Biocoll. Then, RBCs were lysed with hypotonic water or 0.2% sodium chloride (NaCl). Immediately after isolation, harvest, viability, size, granularity, purity, and CD11b expression as a marker for granulocytes was analyzed by flow cytometry. In addition, as a marker for activation and reactivity of the granulocytes, we stimulated cells with phorbol-myristate-acetate (PMA) to evaluate the release of reactive oxygen species. Furthermore, extracellular trap (ET) formation was investigated by confocal immunofluorescence microscopy in untreated control cells and cells treated with the cholesterol-depleting agent methyl-ß-cyclodextrin. We did not find a significant difference in percentage of dead cells when comparing the two anticoagulants or the different RBCs lysis methods. However, the percentage of granulocytes in the harvested population was significantly less using lithium heparin blood as anticoagulant compared to K3EDTA. The granulocytes harvested from lithium heparin blood and water lysis exhibited higher clumping and pre-activation of unstimulated control cells as indicated by isolation of doublet cells, increased CD11b expression, increased oxidative burst and higher amount of ET releasing cells. Furthermore, the combination of K3EDTA as anticoagulant and NaCl as RBCs lysis method revealed the lowest variability and highest difference between untreated and methyl-ß-cyclodextrin treated cells when quantifying ET formation. In conclusion, density gradient centrifugation of K3EDTA-blood resulted in higher purity of bovine granulocytes compared to lithium heparin-blood. In contrast to water lysis, NaCl lysis method is recommended to avoid pre-activation of cells which may occur during hypotonic water lysis.